Weddings - Lindop, Christine (Oxford University Press, 2011)
The bride wore a long white dress, with flowers in her hair. After the wedding, there was a party, and people gave presents to the bride and groom.’ This wedding was nearly two thousand years ago, in Rome. Some things don’t change. But some things do. Today you can have a wedding on a mountain, or under the sea, or ’Elvis’ can sing for you. And different things happen in different places. Little birds made of paper, small trees, money in the bride’s shoe, and lots of noise - they are all important for weddings somewhere. Welcome to the wonderful world of weddings!